Thermoluminescent properties of LaAlO3:C crystals synthesized by solid state reaction applied to UV Dosimetry - neriene alves; wilmar barbosa ferraz; Luiz oliveira Faria (Brazilian Journal of Radiation Sciences)
In this work we have investigated the thermoluminescent (TL) response of carbon doped lanthanum aluminate crystals grown by solid state reaction method. We conducted three syntheses by different combinations of Al2O3, La2O3 and 0.1 wt % of carbon atoms. The 1:1 mixture of aluminum and lanthanum oxide was mixed with 0.1wt.% carbon and annealed at 1700°C for two hours in a hydrogen atmosphere. The X-ray diffraction analysis revealed the formation of the rhombohedral LaAlO3 crystallographic phase. F and F + centers were identified by ultraviolet-visible spectroscopy. Fourier transform infrared spectroscopic data show higher and lower frequencies assigned to AlO6 octahedra in LaAlO3. The UV irradiations were carried out using a commercial 8W UV lamp. Thermoluminescence measurements were performed at a Harshaw 4500 TL reader. The three syntheses were very efficient to obtain carbon doped LaAlO3 crystals with high thermoluminescent output, for low exposure rates of UVR fields.